Understanding Psychological Motives toward Politics: Developing Psychological Orientation Scale towards Politics (POSP-S) for Indonesia - Indro Adinugroho (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2018)
For over 18 years, Indonesia has undergone democracy in every aspect of government decision making. After new order (orde baru) regime fell, Indonesia has changed several regulations to implement democratic principle, such as direct elections for Presidential; Gubernatorial and also local leaders. However, there still few challenges faced by Indonesia. One of those challenges is related to human behavior, which is political participation. In democratic country, one of the primary requirements is voluntarily active participation. Voluntarily means an action without any pressure. Without voluntarily act on participation, a country cannot be listed as democratic country. As an attempt to predict voluntarily participation on politics, psychology has came up with the concept of psychological orientation on politics which represented by three dimensions, political efficacy; political interest and political knowledge. However, different political situation and system among countries are the reason why there is no universal measurement of psychological orientation towards politics. This study aims to construct an instrument as an attempt to measure psychological orientation towards politics in Indonesian context. As an attempt to produce the best items and theoretical model, confirmatory factor analysis (CFA) is applied to examine the contribution of each item towards dimensions. CFA analysis finally generates 21 final items for Psychological Orientation towards Politics Scale that can be applied in Indonesian context.